Levels and Predictors of Anxiety and Depression in Turkish Pregnant Woman During the Covid-19 Pandemic - Aba, Yılda Arzu; Dulger, Ozlem; Sık, Bulat Aytek; Ozolcay, Ozan (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective In addition to being a medical phenomenon, pandemics affect the individual and society on several levels and lead to disruptions. In the pandemic process, different groups in the population, including pregnant women as a defenseless group, are subjected to psychological threat. The present study aimed to determine the levels of anxiety and depression and related factors in pregnant women during the the coronavirus disease 2019 (Covid-19) pandemic.Methods The present cross-sectional study was conducted with 269 pregnant women through face-to-face interviews held in Istanbul, Turkey. Regarding the data collection tools, the Cronbach α reliability coefficient was of 0.90 for the Beck Anxiety Inventory, and of 0.85 for the Beck Depression Inventory.Results Among the participating pregnant women, 30.5% had mild, 17.5% had moderate, and 5.9% had severe anxiety symptoms, whereas 35.3% had mild, 16.7% had moderate, and 2.2% had severe depression symptoms. We found that those who were concerned about their health had 5.36 times (p = 0.04) more risk of developing anxiety, and 4.82 times (p = 0.01) more risk of developing depression than those who were not concerned. Those who had a history of psychiatric disease had 3.92 times (p = 0.02) more risk of developing anxiety than those without it.Conclusion We determined that about half of the pregnant women included in the study had some degree of anxiety and depression during the COVID-19 pandemic. The risk factors for anxiety and depression among the pregnant women were determined as smoking, concerns about health and getting infected with the coronavirus, history of psychiatric disease, and undergoing regular antenatal care.
Keywords: Covid-19; anxiety; depression; pregnant women